Phenotypic and Protein Pattern Characterization and Cluster Analysis of Some Date Palm (Phoenix dactylifera L.) Cultivars in Basrah Governorate - Khassaf, Wafa Hasach (Basrah Journal Of Date Palm Research, 2024)
This study was conducted to characterize ten cultivars of date palm (Phoenix dactylifera L.) grown in Basrah Governorate, focusing on protein patterns and the morphological, floral, and physical traits of fruits and seeds. Cluster analysis was used to determine the similarities and differences among the studied cultivars, which included: Howazaoui, Bream, Hadal, Khesab, Owedi, Shukr, Nabati, Maktoum, Shuwethi, and Khadhrawi. The cluster analysis of vegetative traits grouped the cultivars into two main clusters: the first included Shukr, Howazaoui, and Shuwethi, while the second included the remaining cultivars. A high degree of similarity was observed between Owedi and Maktoum, followed by Nabati and Khadhrawi. For floral traits, distinct groupings were identified: Owedi and Maktoum formed a separate cluster, while Khadhrawi, Khesab, and Hadal formed another, and Nabati, Maktoum, Howazaoui, Bream, and Hadal were grouped together in a third cluster. Regarding the physical traits of the fruits, the Bream cultivar was isolated in a single group, while the other cultivars were grouped together. The highest similarity was observed between Khadhrawi and Shuwethi, as well as between Owedi and Shukr. For protein patterns, the cultivars were divided into two main clusters: the first included Nabati, Khadhrawi, Bream, Hadal, and Shukr, while the second included the remaining cultivars. A notable similarity was found between Nabati and Khadhrawi, followed by Shukr and Hadal. The statistical analysis indicated a significant effect of the cultivar factor on most of the vegetative, floral, and physical traits studied, except for the number of spadices, which showed no significant effect in distinguishing between cultivars